2018
DOI: 10.1002/ccd.27820
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of balloon aortic valvuloplasty in non‐TAVI centers: The “BAV for life” experience

Abstract: BAV is a safe and effective procedure that can be performed by trained operators in centers not performing TAVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…BAV can be considered as a bridge‐to‐decision in high‐risk patients with AS 5 . Published studies have reported that low LV function is an independent predictor of mortality after BAV 6,7 . Additionally, aortic regurgitation after BAV due to the bicuspid anatomy was also factored in during the discussion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAV can be considered as a bridge‐to‐decision in high‐risk patients with AS 5 . Published studies have reported that low LV function is an independent predictor of mortality after BAV 6,7 . Additionally, aortic regurgitation after BAV due to the bicuspid anatomy was also factored in during the discussion.…”
Section: Discussionmentioning
confidence: 99%
“…5 Published studies have reported that low LV function is an independent predictor of mortality after BAV. 6,7 Additionally, aortic regurgitation after BAV due to the bicuspid anatomy was also factored in during the discussion. In our patient, as there was no evidence of ischemic or nonischemic cardiomyopathy, poor LV function was deemed secondary to severe AS.…”
Section: Introductionmentioning
confidence: 99%
“…Besides elective indications for BAV, it is nowadays pre‐dominantly performed as an emergency treatment in the critical ill due to decompensated AS 24‐26 . Those patients do not necessarily have an elaborate MDCT or a 3‐D TOE sizing protocol completed and morbidity and mortality, regardless of the interventional strategy, are extremely high.…”
Section: Discussionmentioning
confidence: 99%
“…In biomedical research, big data is used for electronic health record (EHR) considered “relevant” to the understanding of health and disease, including clinical, imaging, omic, data from internet use and wearable devices, and others (13). The basic principle is to make the whole biomedical practice “evidence generating” without the need to design and conduct ad hoc studies (13, 14). The most popular description for big data was proposed by Doug Laney in 2001 and is known in the academic world as the “3Vs”: volume, variety, and velocity (15).…”
Section: Big Health Data: What Are They?mentioning
confidence: 99%